Volatilomics of raspberry fruit germplasm by combining chromatographic and direct-injection mass spectrometric techniques - Farneti, Brian; Khomenko, Iuliia; Ajelli, Matteo; Wells, Karen Elizabeth; Betta, Emanuela; Aprea, Eugenio; Giongo, Lara; Biasioli, Franco (Frontiers in Molecular Biosciences, 2023)
The application of direct-injection mass spectrometric (DI-MS) techniques, like Proton Transfer Reaction Time of Flight Mass Spectrometry (PTR-ToF-MS) has been suggested as a powerful phenotyping tool for destructive and non-destructive assessment of fruit volatilome in both genetic and quality-related studies. In this study the complexity of raspberry aroma was explored by an exhaustive untargeted VOC analysis, done by combining SPME-GC-MS and PTR-ToF-MS assessments with multi-block discriminant analysis using the DIABLO mixOmics framework. The aim was to acquire a comprehensive characterization of the raspberry volatilome according to different fruit ripening stages (pink, ripe and overripe) and genetic differences (50 accessions), as well as to investigate the potential of PTR-ToF-MS as a rapid and high throughput VOC phenotyping tool to address issues related to raspberry fruit quality. Results of this study demonstrated the complementarity between SPME-GC-MS and PTR-ToF-MS techniques to study the raspberry aroma composition. The use of PTR-ToF-MS resulted particularly suited to generating reliable raspberry VOC fingerprints mainly due to a reduced compound fragmentation and precise concentration estimation. In addition, the high collinearity between isomers of monoterpenes and norisoprenoids, discovered by GC analysis, reduces the analytic limitation of PTR-ToF-MS of not being able to separate isomeric molecules. The high similarity between the VOC matrices obtained by applying PTR-ToF-MS and SPME-GC-MS confirmed the possibility of using PTR-ToF-MS as a reliable VOC phenotyping tool in those investigations that require a detailed VOC profile characterization of a broad number of raspberry fruit. In addition, the exploitation of the genetic variability existing within the investigated germplasm collection allowed the identification of the best performing cultivars, based on VOCs variability, to be used as superior parental lines for future breeding programs.